Pulverized coal ignition testing under air-fired conditions using the Zelkowski method: comparison of coals of different rank and provenience. (August 2017) - Becker, A.; Schiemann, M.; Scherer, V.; Haxter, D.; Mayer, J.
Abstract: Ignitability, which is directly related to flame stability, is an important factor in pulverized coal combustion. In the current work, a laboratory test rig for comparative measurement of coal ignition properties is described. It has been designed for standard coal combustion conditions using air as oxidant. The measurement principle is described on the basis of experimental data gained from four "standard coals" of different rank and provenience. The results show the general tendencies known for the influence of coal rank. Higher volatile content in coal leads to lower ignition temperature.